Assessment of Microgravity Anomalies of Soil Structure for Geotechnical 2D Models - Arisona, Arisona; Nawawi, Mohd; Khalil, Amin E.; Abdulrahman, Abdullahi (UIR PRESS, 2018)
A microgravity investigation on bedrock topography was conducted at Maluri Park in Kuala Lumpur, Malaysia. The study characterized the subsurface structure to delineate soil structure for the geotechnical application. Cross-section modelling of the residual anomaly generated the Maluri Bouguer Anomaly model for test site. The 2D microgravity models produced the contour map, displaying the characterization due to density contrast in rock types while mapping the subsurface geological structure at different depths. Moreover, a synthetic model was initiated with the assumption of lateral distance on the left and right sides taken at 50 m and a depth of 60 m. The results of modeling confirmed that the soil and rock type composition on models test site, i.e: topsoil (1.1 g/cm3), soil (1.8 g/cm3), clay (1.63 g/cm3), gravel (2.0 g/cm3), sand (1.7 g/cm3), shale (2.40 g/cm3), sandstone (2.76 g/cm3) and limestone (2.9 g/cm3). The 2D gravity synthetic model show a good match with the observed microgravity data.